Technology-Integrated Discovery Learning for Elementary Mathematical Understanding and Engagement - Suhardi Usman; Edy Waluyo; Sri Supiati (IJE : Interdisciplinary Journal of Education, 2026)
This study developed and evaluated a technology-integrated discovery learning model to strengthen elementary students' mathematical conceptual understanding and learning engagement. Although digital technologies are increasingly available in primary classrooms, mathematics instruction frequently remains dominated by teacher-centered practices that prioritize procedural fluency over conceptual reasoning. To address this problem, the study employed a Research and Development design guided by the ADDIE framework, which comprises analysis, design, development, implementation, and evaluation. The participants included fifth-grade elementary students involved in small-group and large-group trials, a classroom teacher, and three expert validators specializing in mathematics education, instructional media, and language. Data were collected using expert validation sheets, teacher and student practicality questionnaires, classroom observations, and pretest-posttest assessments. The data were analyzed through descriptive statistics, normalized gain analysis, and paired-sample t-tests. The findings indicate that the developed model achieved a high level of validity, with an average expert validation score of 90%. Teacher and student responses also showed that the model was highly practical, with an average practicality score of 89%. Furthermore, implementation of the model substantially improved students' mathematics learning outcomes, as reflected in high N-gain scores of 0.81 in the small-group trial and 0.75 in the large-group trial. Paired-sample t-tests confirmed significant differences between pretest and posttest scores (p < .05). These findings suggest that integrating discovery learning with digital technology offers a pedagogically sound, student-centered, and conceptually meaningful approach to elementary mathematics instruction.